Caffeine: Cognitive and Physical Performance Enhancer or Psychoactive Drug? - Cappelletti, Simone; Daria, Piacentino; Sani, Gabriele; Aromatario, Mariarosaria (Current Neuropharmacology, 2015)
Caffeine use is increasing worldwide. The underlying motivations are mainly concentration and memory enhancement and physical performance improvement. Coffee and caffeine-containing products affect the cardiovascular system, with their positive inotropic and chronotropic effects, and the central nervous system, with their locomotor activity stimulation and anxiogenic-like effects. Thus, it is of interest to examine whether these effects could be detrimental for health. Furthermore, caffeine abuse and dependence are becoming more and more common and can lead to caffeine intoxication, which puts individuals at risk for premature and unnatural death. The present review summarizes the main findings concerning caffeine’s mechanisms of action (focusing on adenosine antagonism, intracellular calcium mobilization, and phosphodiesterases inhibition), use, abuse, dependence, intoxication, and lethal effects. It also suggests that the concepts of toxic and lethal doses are relative, since doses below the toxic and/or lethal range may play a causal role in intoxication or death. This could be due to caffeine’s interaction with other substances or to the individuals&apos preexisting metabolism alterations or diseases.be due to caffeine’s interaction with other substances or to individuals’ pre-existing diseases or metabolism alterations.
Keywords: toxicity